2017
DOI: 10.1063/1.4977503
|View full text |Cite
|
Sign up to set email alerts
|

The wasp-waisted hysteresis loop and exchange bias in multiferroic BaNiF4

Abstract: Multiferroic BaNiF4 has been fabricated by hydrothermal method. The bifurcation between zero field cooling (ZFC) and field cooling (FC) temperature dependent magnetization (M-T) curves starts at 150 K, indicating the 2D antiferromagnetic (FM) transition. A further upturn of magnetization has been observed below 68 K in FC M-T curve, corresponding to the emergence of 3D AFM structure. Wasp-waisted hysteresis loop was observed under 130 K, which is explained by that the AFM aligned net spins from the canting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Such type of the hysteresis was observed for many different magnetic materials: for example, for Dy Quite close for us example with similar type of hysteresis loop has also been observed for 2D multiferroic compound BaNiF 4 [67]. According to the theoretical calculations this system is canted antiferromagnet with weak interaction between different sheets [68], leading to low magnetic ordering temperature and pronounced two-dimensional behaviour.…”
Section: B Static Magnetic Propertiessupporting
confidence: 74%
“…Such type of the hysteresis was observed for many different magnetic materials: for example, for Dy Quite close for us example with similar type of hysteresis loop has also been observed for 2D multiferroic compound BaNiF 4 [67]. According to the theoretical calculations this system is canted antiferromagnet with weak interaction between different sheets [68], leading to low magnetic ordering temperature and pronounced two-dimensional behaviour.…”
Section: B Static Magnetic Propertiessupporting
confidence: 74%
“…As expected, no order is observed between the planes with a two-dimensional Heisenberg Hamiltonian and a local single ion anisotropy. As in the literature the 68.4 K transition has been associated with a 3D ordering [18,22], we added dipolar interactions in order to evaluate if some 3D long-range order can be triggered by them. We estimated their energy contribution using the Hamiltonian :…”
Section: Magnetic Ordermentioning
confidence: 99%
“…Neutron scattering experiments, performed at 4.2 and 77 K, showed that the AFM magnetic order has a propagation vector q M = ( 1 2 , 1 2 , 0) at low temperature [21]. At higher temperatures a broad maximum is observed in the magnetic susceptibility that is sometimes attributed to a two-dimensional ordering [22]. C. Ederer et al [23] predicted the existence of a small canting of the magnetic moments in BaNiF 4 which has its origin in the polar distortion, through a proposed Dzyaloshinskii-Moriya (DM) interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Although at first glance the magnetic moment could be seen to be weak, it could be amplified by layerengineering and growing a ferromagnetic layer on the top of it as demonstrated through the exchange-bias effect [48] in [Co/Pd(Pt)]/Cr 2 O 3 [49] and NiFe/h-YMnO 3 (LuMnO 3 ) [50] but also in the Barium-based family of AM F 4 crystals with M = Ni and Mn [51,52]. Therefore, bilayered EB-effect could be combined to bring about a novel electrically-controlled magnetic system based-on BaCuF 4 [48].…”
mentioning
confidence: 99%